Tandem repeats of the extracellular domain of Matrix 2 influenza protein exposed in Brucella lumazine synthase decameric carrier molecule induce protection in mice - Alvarez, Paula (2013)
The antigenic variation of influenza virus represents a major prevention problem. However, the ectodomain of the protein Matrix 2 (M2e) is nearly invariant in all human influenza A strains and has been considered as a promising candidate for a broadly protective vaccine because antibodies to M2e are protective in animal models. In this work we evaluated the possible use of Brucella abortus lumazine synthase protein (BLS), a highly immunogenic decameric protein, as a carrier of the M2e peptide. Chimeric proteins generated by the fusion of one or four in tandem copies of M2e to BLS were efficiently expressed in Escherichia coli and assembled in decameric subunits similarly to the wild type BLS enzyme, as demonstrated by the comparative circular dichroism spectra and size exclusion chromatography and static light scattering analysis. The M2e peptides were stably exposed at the ten N-terminal ends of each BLS molecule. Immunization of mice with purified chimeras carrying only one M2e (BLS-M2e) copy elicited a significant humoral immune response with the addition of different adjuvants. The fusion of four in tandem copies of the M2e peptide (BLS-4M2e) resulted in similar levels of humoral immune response but in the absence of adjuvant. Survival of mice challenged with live influenza virus was 100% after vaccination with BLS-4M2e adjuvanted with Iscomatrix(®) (P<0.001) and 80% when adjuvanted with alum (P<0.01), while the chimera alone protected 60% of the animals (P<0.05). The approach described in this study is intended as a contribution to the generation of universal influenza immunogens, through a simple production and purification process and using safe carriers that might eventually avoid the use of strong adjuvants.